Firm property rights, bargaining, and internalization - Lisandro Abrego; John Whalley (The University of Western Ontario, Department of Economics, 2002)
Coase's seminal 1960 paper on externalities is associated with the so-called Coase Theorem which is stated in the literature in many forms. However, its main thrust was less to state a theorem than to challenge Pigou's earlier insistence on the need for government intervention through Pigouvian taxes to achieve internalisation of externalities. Coase argued instead that private party bargaining can be relied upon to internalise externalities, but equally insisted that establishing clear and firm property rights is a precondition to successful internalisation achieving bargaining. Similar thinking has lead to clear definitions of property rights becoming a key part of World Bank conditionality in the environmental area. This paper discusses the underpinnings of this position, arguing that it is little researched and subject to challenge. We first show how Coase only considered one type of property right, and where others such as compensation rights are allowed for the property right assignment will itself directly achieve internalisation with no need for further bargaining. We also show how ambiguous property rights can dominate a clear assignment of property rights for a case where recipients of damage can move to avoid damage, but must remain and actually receive damage in order to be recipients of compensation. Rights to either polluters to pollute, or to recipients of damage to compensation create a distortion; and either outcome is dominated by no assignment of property rights, but a tax on polluters (Pigouvian tax) with revenues redistributed equally to the whole population.
Keywords: 330